Implementation of Demonstration Methods to Improve Science Learning Results for Violent Students of Sdn 01 Simpur - Junianto Safi’i (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of the classroom action research in this study was to improve the learning outcomes of Kalas VI students in science learning basic competence to identify magnetic and non-magnetic objects through the demonstration method. This research was conducted in two cycles, with each cycle consisting of one meeting. The procedures in classroom action research include planning, acting, observing, reflecting. Based on the data analysis of the research results, it can be concluded that the use of the demonstration method in science learning basic competence to identify magnetic and non-magnetic objects, is proven to improve learning outcomes of class VI SDN 01 Simpur students with an average value of 60 up to 75 and the percentage of students who have completed from 45% to 88%. The use of the Demonstration method can also increase student learning activeness in science learning, from 18 active students to 29 active students and the percentage of active students from 58% to 92%.